Patterns of Complementary Medicine Utilization in Patients With Breast Cancer and Colorectal Cancer: A Cross-Sectional Study at a Tertiary Referral Hospital in Yogyakarta, Indonesia - Juan Adrian Wiranata; Susanna Hilda Hutajulu; Norma Dewi Suryani; Rr. Rayna Adya Harvianti; Ashifa Jasmine; Yufi Kartika Astari; Herindita Puspitaningtyas; Mardiah Suci Hardianti; Yayi Suryo Prabandari (JCO Global Oncology)
PURPOSEThe utilization of complementary medicine (CM) in patients with cancer brings substantial challenges to optimal cancer care by posing a risk of side effects and drug interaction, and might delay cancer care delivery. We aimed to characterize the patterns and predictors of CM utilization in patients with breast cancer (BC) and patients with colorectal cancer (CRC), and the impact on presentation and diagnosis interval.METHODSWe interviewed patients with BC and patients with CRC using a semistructured questionnaire to gather sociodemographic, clinical, presentation and diagnosis interval, and CM utilization data. The domains of CM used were categorized according to the classification of the National Institutes of Health/National Center for Complementary and Integrative Health.RESULTSOne hundred forty-two patients with BC and 227 patients with CRC (N = 369) were included. The prevalence of CM utilization was 69.9%, with biologically based therapies being the most commonly used type. Younger age, higher educational attainment, and a greater number of health facility visits before diagnosis were significantly associated with higher odds of CM utilization (odds ratio [OR], 2.05 [95% CI, 1.19 to 3.54]; P = .010; OR, 1.07 [95% CI, 1.02 to 1.11]; P = .007, respectively). The diagnosis interval was significantly longer in patients who used CM compared to nonusers (incidence rate ratio [IRR], 2.74 [95% CI, 1.77 to 4.26]; P < .001). A greater number of CM modalities used were significantly associated with longer presentation and diagnosis intervals (IRR, 1.68 [95% CI, 1.06 to 2.66]; P = .027; IRR, 1.62 [95% CI, 1.04 to 2.52]; P = .033, respectively).CONCLUSIONA significant portion of the local patients with BC and patients with CRC used CM. CM utilization was associated with age, education, number of health facility visits, and prolonged diagnosis interval. These findings underscore the need for CM disclosure among patients for better patient education and monitoring.